Effect of foliar application of iron and zinc on nutrient uptake and grain yield of wheat under different irrigation regimes (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was carried out to study the zinc-iron relationship in wheat (BARI Gom-26) plant grown under water stress condition in the field near net house of Soil Science Division, BARI, Joydebpur, Gazipur, during November 2015 to March 2016. The experiment was designed in a split plot on sixteen treatments comprising four irrigation treatments (regular irrigation, stopping irrigation at crown root initiation, stopping irrigation at booting stage and stopping irrigation at grain filling stage) and four foliar application of zinc and iron (control, 0.05% of zinc, 0.05% of iron and 0.05% of zinc +0.05% of iron). Zinc sulphate monohydrate (ZnSO4. H2O) and ferrous sulphate (FeSO4. H2O) were used as a source of Zn and Fe. The highest yield (4.01 t ha-1) was recorded in stopping irrigation at grain filling stage which was identical with regular irrigation. Water stress at crown root initiation stage had the most negative effect on growth and yield. Foliar application of zinc and iron played a major role on yield and yield components of wheat at later stages of growth. The results obtained from the present research showed that iron and zinc spray increased grain yield and quality of wheat and improved the effects caused by drought stress.Bangladesh J. Agril. Res. 43(3): 395-406, September 2018